A robust one-dimensional approach for the performance evaluation of turbines driven by pulsed detonation combustion. (15th November 2021) - Asli, Majid; Garan, Niclas; Neumann, Nicolai; Stathopoulos, Panagiotis
Abstract: Among the solutions to reduce emissions from stationary gas turbines, replacing conventional combustion through pressure gain combustion is one of the most promising options. Nevertheless, coupling pressure gain combustion with a turbine can result in increased losses within the cycle, mainly because of the resulting very unsteady turbine inflow conditions. A reliable simulation tool can help to overcome this challenge and optimize turbine geometries and designs for the specific application. The harsh unsteady flow downstream of pressure gain combustors makes three-dimensional CFD computationally expensive. Thus, the development of a fast computational method is crucial. This paper introduces and explores such an alternative methodology. A one-dimensional Euler gas dynamic approach is combined with blade source terms, computed out of a steady-state turbine meanline analysis. To evaluate the methodology, three-dimensional CFD simulations are performed in parallel and the results are compared with those of the 1D method. The energy extraction of a turbine expander is computed with both methods for three different configurations of pulsed detonation combustor arrays connected at the turbine inlet. The results show that the proposed approach is capable of simulating the turbine in such an unsteady environment accurately. Additionally, it is indicated that around 45% of the total unsteadiness is damped throughout the first blade row, which is almost irrespective of the inlet fluctuation amplitude. Due to its accuracy and very low computational cost, the developed methodology can be integrated into optimization loops in the early design and development stages of turbomachinery for pressure gain combustion applications.